Antibacterial activity of Timsen(®) (n-alkyl dimethyl benzyl ammonium chloride-40%) in scalding and precooling water in poultry slaughterhouses - Lansini, Valmor (J Food Sci Technol, 2017)
The objective of this study was to evaluate the efficacy of a product based on n-alkyl dimethyl benzyl ammonium chloride-40%, marketed as Timsen(®), during scalding and precooling of poultry carcasses in slaughterhouses. To this end, three poultry slaughterhouses (A, B and C) were evaluated. The product was added (200 ppm) to the scalding (58 °C) and precooling water (4 °C), and microbiological analyses were performed of the water and the poultry carcasses before and after Timsen(®) addition. The product controlled the multiplication of aerobic mesophilic microorganisms, both in the scalding as in the precooling water. In a comparison of carcasses soaked in Timsen(®)-treated scalding and precooling water with carcasses soaked in untreated water, the count of aerobic mesophilic microorganisms in the later was higher and thermotolerant coliform was not detected in samples of carcasses soaked in Timsen(®)-treated water. When the scalding and precooling water was not treated with the product, Listeria spp. was isolated from poultry carcasses of two slaughterhouses (A and C), while these microorganisms were not detected when Timsen(®) was applied. The use of Timsen(®) in the scalding and precooling water enhanced the safety and control microbial contamination of poultry carcasses.